Pengaruh Abdominal Stretching Exercise dan Senam Dismenorea Terhadap Intensitas Nyeri Dismenorea pada Remaja Putri di SMA Sindangbarang Tahun 2025 - Saniawati, Saniawati; Rini, Ageng Septa; Hidayani, Hidayani; Nurhayati, Tuti; Meliawati, Resti; Nuraeni, Lia; Saparina, Santi (LPPM Institut Pendidikan Nusantara Global, 2025)
Dysmenorrhea can be described as pain that occurs during menstruation due to excessive release of prostaglandins, causing hyperactivity of uterine contractions and resulting in pain during menstruation. Non-pharmacological measures to treat dysmenorrhea can be done by Abdominal Stretching Exercise and Dysmenorrhea Exercises. The aim of this case study is to identify the effect of Abdominal Stretching Exercise and Dysmenorrhea Gymnastics on reducing the intensity of menstrual pain (primary dysmenorrhea) in adolescents. Research Method This case study uses a quasi-experimental method with a pre-posttest control group design approach. Based on the results of the case study, it was found that there was a difference in reducing the intensity of pain in adolescent girls who were given the Abdominal Streching Exercise and Dysmenorrhea Exercise intervention. The results can be concluded that the Abdominal Streching Exercise and Dysmenorrhea Exercise had an effect on reducing the pain intensity of primary dysmenorrhea in adolescent girls. However, what is very significant in reducing the pain of dysmenorrhea is Abdominal Streching Exercise. Suggestions. It is hoped that the results of this case study can be used as non-pharmacological therapy in dealing with clients who experience menstrual pain (primary dysmenorrhea), increase the knowledge and insight of young women regarding how to deal with menstrual pain (primary dysmenorrhea), can be used as consideration and additional material for future reviewers, and can be used as a guide for future reviewers in continuing case studies about young women who experience menstrual pain (primary dysmenorrhea).